Mengenal fisika modern dan sejarah kemuculannya - Maqshuroh, Khurum (Maliki Interdisciplinary Journal, 2024)
Classical physics began in the year 1800 and continued until 1890. Classical physical principles were developed prior to the introduction of quantum theory and relativity in the years 17 and 19. During this period, new phenomena emerged that cannot be explained by classical physics. This promotes the development of more comprehensive physical concepts, now referred to as contemporary physics.